Myopia: attempts to arrest progression. Issue 11 (1st November 2002) - Saw, S M; Gazzard, G; Au Eong, K-G; Tan, D T H
Abstract : Previous studies have evaluated the efficacy of several interventions to decrease the progression of myopia. These include devices that alter the perception of the visual environment and pharmacological treatments. There is no conclusive evidence thus far that alteration of the pattern of spectacle wear, bifocals, ocular hypotensives, or contact lenses retards the progression of myopia. Several randomised clinical trials have demonstrated that the rate of progression of myopia is lower in children given atropine eye drops than those given placebo. However, atropine is associated with short term side effects such as photophobia and possible long term adverse events including light induced retinal damage and cataract formation. Other more selective antimuscarinic agents such as pirenzipine are presently being evaluated. Further well conducted randomised clinical trials with large sample sizes and adequate follow up designed to evaluate treatments to retard the progression of myopia should be conducted, since the identification of an effective intervention may have a greater public health impact on the burden and morbidity from myopia than the few treatments currently available.